Prediction of UTR5’, CDS AND UTR3’ Splice sites in an unknown DNA sequence - Chaki, Dipankar; Roushan, Tanvir; Chowdhury, Md. Syeed (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.